Cyprus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper analyzes the economic effects of weak claims enforcement for Cyprus. Claims enforcement in Cyprus is considerably less efficient than in most European Union countries. The banking crisis, which led to a spike in the number of pending litigious civil and commercial cases, could be a factor in the low enforcement efficiency. For Cyprus, piecemeal reform of the enforcement framework may have limited success, and a wholesale review is likely needed. Adding updated components may not fit well with the underlying civil procedure. Instead a comprehensive review, with a focus on limiting case suspensions allowed under interim applications and considering an alternative compensation basis for lawyers should be considered.